Utilization of Fermented Corn Cobs Flour in a Pellet-Shaped Ration AgainstMale Local Rabbit Carcasses (Oryctolagus cunniculus) Off Wean - Agung Baskoro; A H Daulay; E Mirwandhono; Yunilas; Y L Henuk (Talenta Publisher, 2018)
Rabbits are livestock that can be used as a source of animal protein and have the potential to have meet national meat needs. Further development is needed whit good quality feed and affordable prices. The study aimed to evaluate feed containing corn cobs which were fermented by MOIYL against carcasses in local rabbits. The study was conducted in Bandar Klippa Deli Serdang Village, North Sumatra Province, in January - March 2018. This study used 20 local rabbits with initial weights of 404.4 ± 9.14 grams and experimental designs using a completely randomized design (CDR), which consisted from 4 treatments and five replications. The treatment consisted of P0 = unfermented ration, P1 = 10%, P2 = 20%, and P3 = 30%. The variables measured were cut weight, carcass weight, and carcass percentage. The results showed that corn cobs fermentation with probiotics MOIYL had a significant effect (P <0.01) and not significant (P> 0.05), increasing corn cobs fermented by MOIYL to a level of 30% increasing slaughter weight and carcass weight, but does not increase the percentage of carcass.